2023
DOI: 10.3390/f14081644
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Brazil’s Forestry Education: Overview of the Forest Engineering Programs

Abstract: Our study aims to provide a comprehensive overview of forestry programs in Brazil, including a comparative analysis with other countries while considering geographical factors. Over the past 25 years, the number of forestry programs in Brazil has increased from 43 to 75, leading to a rise in the annual number of graduates from 850 to 1500. Nevertheless, our findings reveal that only 60% of the available vacancies at universities are filled. On average, each institution enrolls 169 students (from 40 to 360 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Besides this, 100% of the organizations studied recognized a shortage of professionals prepared for the current job requirements. In addition, all organizations pointed out that new graduates lack training in soft skills [10]. The survey also showed that new professionals displayed an adequate technological background (58%) and were autonomous in learning (58%), possibly related to a result pointed out by 65% of the interviewees who recognize a lack of adequate training in the management of operations and field activities for new professionals.…”
Section: Trends and Current Scenario Of Forest-engineering Jobs In Ip...mentioning
confidence: 96%
See 2 more Smart Citations
“…Besides this, 100% of the organizations studied recognized a shortage of professionals prepared for the current job requirements. In addition, all organizations pointed out that new graduates lack training in soft skills [10]. The survey also showed that new professionals displayed an adequate technological background (58%) and were autonomous in learning (58%), possibly related to a result pointed out by 65% of the interviewees who recognize a lack of adequate training in the management of operations and field activities for new professionals.…”
Section: Trends and Current Scenario Of Forest-engineering Jobs In Ip...mentioning
confidence: 96%
“…This sector hires a significant proportion of forest engineers in Brazil-circa 35% of graduates [19]; nevertheless, the group of forestry-based companies could be overrepresented. Another possible limitation is that in the fourth survey, we decided to collect the opinion of professionals currently employed in a job related to the forestry program, which represented most new graduates in Brazil (about 85%) [10]. Therefore, the opinions of unemployed professionals (about 6%) or those that are working in other fields (6%) could point to other aspects to improve in the course curricula at universities.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forestry schools emerged in 1811 in Germany, seeking to manage the use of forest resources that had been exploited in a disorderly way [1]. In Brazil, the first program was started in 1960 at the Federal University of Viçosa (Minas Gerais State), and currently there are 75 programs in the country, training around 1500 professionals per year [2].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the area occupied by planted forests encompasses 3 million ha in the southeast, while in the northeast, planted forests cover only 1 million ha, despite the significant potential of the latter. Furthermore, the number of forest engineering programs varies [2] from 24 programs in the southeastern region to 12 programs in the northeastern region.…”
Section: Introductionmentioning
confidence: 99%